2013
DOI: 10.3389/fnins.2013.00189
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrhic victories: the need for social status drives costly competitive behavior

Abstract: Competitive behavior is commonly defined as the decision to maximize one's payoffs relative to others. We argue instead that competitive drive derives from a desire for social status. We make use of a multi-player auction task in which subjects knowingly incur financial losses for the sake of winning auctions. First, we show that overbidding is increased when the task includes members of a rival out-group, suggesting that social identity is an important mediator of competitiveness. In addition, we show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 51 publications
0
27
0
2
Order By: Relevance
“…The motivation to attain higher status (i.e., the desire to 'win') is likely a key psychological factor involved in overbidding. In one study 26 male participants provided saliva samples in the late afternoon or early evening and made decisions in a laboratory auction task [16 ]. There was a basal testosterone  basal cortisol interaction such that testosterone was positively related to overbidding among low-cortisol individuals but not high-cortisol individuals.…”
Section: Overbidding In Auctionsmentioning
confidence: 98%
“…The motivation to attain higher status (i.e., the desire to 'win') is likely a key psychological factor involved in overbidding. In one study 26 male participants provided saliva samples in the late afternoon or early evening and made decisions in a laboratory auction task [16 ]. There was a basal testosterone  basal cortisol interaction such that testosterone was positively related to overbidding among low-cortisol individuals but not high-cortisol individuals.…”
Section: Overbidding In Auctionsmentioning
confidence: 98%
“…Peer competition is also a typical type of peer interaction, and recent work has suggested that winning/losing in a competition is an intrinsic social reward/punishment (van den Bos et al, 2013a,b). However, the effects of peer competition on adolescent risk-taking have remained elusive and our results provide a clue toward answering this question, at the same time demonstrating the utility of smartphone technology to explore these heretofore types of hard to reach questions.…”
Section: Discussionmentioning
confidence: 99%
“…While conducting comparable experiments for adults would not be easy given that there are no exact counterparts to classmates or classrooms (the office environment, while potentially applicable, presents many different dynamics and variables), it may be possible for young adults, i.e., college students. Second, all participants were males; comparison with females would also be interesting especially given the suggested relationships between testosterone and competitive behavior (Mazur and Booth, 1998; van den Bos et al, 2013a; Casto and Edwards, 2016). Third, all the participants in the present study were students at the same junior high school, and results might reflect specific characteristics of that school.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired salience attribution in psychopathy may also explain another curious finding-the gratuitous squandering of possessions and resources. Cleckley puzzled over this self-destructive behavior, "the psychopath [sic] often makes little or no use of what he attains as a result of deeds that eventually bring him to disaster (p. 320) (see also van den Bos et al [88]). " Psychopathy appears to impair both caring for other people and caring for possessions.…”
Section: Why Do They Do That?mentioning
confidence: 99%